Hemin treatment drives viral reactivation and plasma cell differentiation of EBV latently infected B cells. - Anna M Burnet; Tonya Brunetti; Rosemary Rochford (PLoS Pathogens, 2023)
Epstein-Barr virus (EBV) and Plasmodium falciparum have a well described role in the development of endemic Burkitt lymphoma (BL), yet the mechanisms involved remain unknown. A major hallmark of malarial disease is hemolysis and bystander eryptosis of red blood cells, which causes release of free heme in large quantities into peripheral blood. We hypothesized that heme released during malaria infection drives differentiation of latently infected EBV-positive B cells, resulting in viral reactivation and release of infectious virus. To test this hypothesis, we used the EBV-positive Mutu I B-cell line and treated with hemin (the oxidized form of heme) and evaluated evidence of EBV reactivation. Hemin treatment resulted in the expression of EBV immediate early, early and late lytic gene transcripts. In addition, expression of CD138, a marker of plasma cells was co-expressed with the late lytic protein gp350 on hemin treated Mutu I cells. Finally, DNase-resistant EBV DNA indicative of virion production was detected in supernatant. To assess the transcriptional changes induced by hemin treatment, RNA sequencing was performed on mock- and hemin-treated Mutu I cells, and a shift from mature B cell transcripts to plasma cell transcripts was identified. To identify the mechanism of hemin-induced B cell differentiation, we measured levels of the plasma cell transcriptional repressor, BACH2, that contains specific heme binding sites. Hemin treatment caused significant degradation of BACH2 by 24 hours post-treatment in four BL cell lines (two EBV positive, two EBV negative). Knockdown of BACH2 in Mutu I cells using siRNAs significantly increased CD138+gp350+ cells to levels similar to treatment with hemin. This suggested that hemin induced BACH2 degradation was responsible for plasma cell differentiation and viral reactivation. Together, these data support a model where EBV reactivation can occur during malaria infection via heme modulation, providing a mechanistic link between malaria and EBV.